2017
DOI: 10.1038/s41598-017-17796-y
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid type 2 receptors in dopamine neurons inhibits psychomotor behaviors, alters anxiety, depression and alcohol preference

Abstract: Cannabinoid CB2 receptors (CB2Rs) are expressed in mouse brain dopamine (DA) neurons and are involved in several DA-related disorders. However, the cell type-specific mechanisms are unclear since the CB2R gene knockout mice are constitutive gene knockout. Therefore, we generated Cnr2-floxed mice that were crossed with DAT-Cre mice, in which Cre- recombinase expression is under dopamine transporter gene (DAT) promoter control to ablate Cnr2 gene in midbrain DA neurons of DAT-Cnr2 conditional knockout (cKO) mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
152
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 130 publications
(166 citation statements)
references
References 69 publications
13
152
0
1
Order By: Relevance
“…Our goal here was to summarize the protocol used to measure alcohol preference in combination with stress-induced alcohol consumption. We also provide evidence that the endocannabinoid system plays a role in alcohol preference following dopaminergic neuron specific deletion of CB2Rs in the mouse model (Liu et al ., 2017). …”
Section: [Background]supporting
confidence: 55%
See 1 more Smart Citation
“…Our goal here was to summarize the protocol used to measure alcohol preference in combination with stress-induced alcohol consumption. We also provide evidence that the endocannabinoid system plays a role in alcohol preference following dopaminergic neuron specific deletion of CB2Rs in the mouse model (Liu et al ., 2017). …”
Section: [Background]supporting
confidence: 55%
“…We are also thankful for the technical assistant of Sneha Tammareddy, Eugene Dennis, Branden Sanabria, Paola Velandia, Steve Gross, and Monika Chung while working in the laboratory of ESO. This protocol and figures are adapted from our previous work (Liu et al , 2017). …”
Section: Acknowledgmentsmentioning
confidence: 99%
“…These findings are consistent with an early report indicating that deletion of CB 2 receptors in CB 2 ‐KO mice failed to alter Δ 9 ‐THC‐induced hypothermia and immobility (Buckley et al, ). Furthermore, Onaivi et al () have recently reported that selective deletion of CB 2 receptors on dopaminergic neurons reduced WIN55212‐2‐induced catalepsy and altered WIN55212‐2‐induced analgesia (as assessed in a tail flick test) but had no effect on WIN55212‐2‐induced hypothermia and hypoactivity (Liu et al, ), which provides additional evidence supporting brain CB 2 receptor involvement in cannabinoid‐induced pharmacological effects. We note that pretreatment with AM251 almost completely blocked, while AM630 only partially attenuated Δ 9 ‐THC‐ or WIN55212‐2‐induced analgesia and catalepsy, suggesting that CB 1 receptors play a more important role than CB 2 receptors in cannabinoid action.…”
Section: Discussionmentioning
confidence: 95%
“…We have recently reported that brain CB 1 and CB 2 receptors mediate cannabis reward versus aversion, respectively, as assessed in a brain stimulation reward paradigm in rats (Spiller et al, ). Selective deletion of CB 2 receptors from midbrain dopamine neurons altered multiple behavioural effects in mice produced by WIN55212‐2, a synthetic cannabinoid (Liu et al, ), suggesting a possible involvement of brain CB 2 receptors in cannabinoid‐induced tetrad effects. In addition, GPR55, another putative cannabinoid receptor (Baker, Pryce, Davies, & Hiley, ; Moriconi, Cerbara, Maccarrone, & Topai, ), was also found in brain regions involved in locomotion and nociception (Martínez‐Pinilla et al, ; Ryberg et al, ; Wu et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation